Breaking barriers: enhancing CAR-armored T cell therapy for solid tumors through microenvironment remodeling - Andreou, Tereza; Neophytou, Constantina; Kalli, Maria; Mpekris, Fotios; Stylianopoulos, Triantafyllos (Frontiers in Immunology, 2025)
Whilst chimeric antigen receptor (CAR) T cell therapy has emerged as a revolutionary immunotherapeutic approach for hematological malignancies in recent years, several challenges remain to potentiate the efficacy of CAR T cell therapies for solid tumors. Here, we focus on the obstacles posed by the tumor microenvironment that hinder the effective trafficking, infiltration and precise tumor targeting by engineered cells. We discuss how the tumor microenvironment presents a physical barrier that needs to be surpassed for effective cell therapies and ongoing efforts in designing innovative CAR T cell therapies with enhanced tumor-targeting precision, improved stability, and overcoming on-target off-tumor toxicity are presented. We focus on recent advances in clinical and preclinical settings to reprogram the immunosuppressive tumor microenvironment, including stroma and blood vessel normalization strategies that can be leveraged to improve the tumor-homing and tumor-targeting potential of engineered therapeutic cells for immuno-oncology applications. As the endeavors for innovative CAR designs continue, we are entering an exciting era in the field of personalized cell therapies offering renewed hope to patients with hard-to-treat solid tumors.